LO007: A pragmatic randomized and controlled evaluation of nurse-initiated protocols. (2nd June 2016) - Douma, M.J.; Dochartiagh, D. O; Drake, C.A.; Smith, K.E.
Abstract : Introduction: Emergency department (ED) overcrowding is a common and complicated challenge for EDs worldwide. Nurse-initiated protocols, diagnostics and/or treatments implemented by nurses prior to patients being seen by a physician or nurse practitioner, have been suggested as a potential strategy to improve patient flow.Methods: This randomized, pragmatic, controlled evaluation of 5 nurse-initiated protocols occured in a crowded inner-city ED. Six physicians and 44 registered nurses, 3 clinical nurse educators and 3 unit managers were involved in revising 5 patient-complaint focused protocols prior to evaluation. Thirty (30/180) emergency nurses were provided 1 hour of training on inclusion and exclusion criteria, procedure and evaluation methods. Data was abstracted in a manner concealing patient allocation. Primary outcomes evaluated included time to diagnostic test, treatment, consultation or ED length of stay. This evaluation was completed following both the CONSORT and SQUIRE guidelines.Results: Time to acetaminophen for the intervention group (n=11) was 1h:04 min on average (95%CI 30min to 1h:37min) whereas the control group (n=9) was 3h:35min (95%CI 2h:21min to 4h:48min). The average length of stay of a suspected fractured-hip in the intervention group (n=5) was 3h:34min (95%CI 1h:49min to 5h:19min) and 7h:34min for the control group (n=4) was (95%CI 5h:26min to 9h:42min). Time to troponin in the intervention group (n=29) was one quarter (average 48min, 95% CI 32min to 64min) of the time it was in the control group (n=14) (average 3h:16min, 95%CI 1h:53min to 4h:39min; p < 0.001). The vaginal bleeding in pregnancy protocol reduced length of stay by roughly fifty-percent; the intervention group (n=11) had a length of stay of 4h:57min (95%CI 3h:46min to 6h:08min) compared to 8h:33min (95% CI 6h:23min to 10h:44min) for the control (n=7) (p < 0.001). There was no statistical difference in the length of stay for patients who received protocolized diagnostics for abdominal pain.Conclusion: Targeting specific patient groups with carefully written protocols can improve the timeliness of care. A cooperative and collaborative interdisciplinary group are essential to success. Having a system in place to ensure ongoing quality in protocol application and interdisciplinary support has proven more difficult than improving the primary outcomes in this evaluation.